Effect of Valsalva Maneuver in Attenuating Spinal Needle Puncture Pain - Haider Ali Khan, Arsalan Jamil, Zahid Aziz Soomro, Tahir Ali, M. Aneeque Alam Khan, Asim Javed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the frequency of pain in patients undergoing elective lower limb surgery between valsalva maneuver versus control group during spinal anesthesia. Study Design: Randomized controlled trial Place and Duration of Study: Department of Anesthesia, Dow University of Health Sciences, Civil Hospital, Karachi from 1st June 2018 to 30th November 2018. Methodology: All patients aged 25 to 50 years of either sex having ASA status I and II undergoing for surgery in sitting position under sub-arachnoid block through midline approach were taken as study participants. Randomization was done and divided in two groups; Group A were those who did not perform valsalva group B were those who perform valsalva. Puncture pain was assessed and measured by visual analogue scale in which 0 indicates no pain whereas, 10 is considered as most painful. Results: The mean age was 39.76±8.43 years. There were 31 (51.7%) males and 29 (48.3%) females with body mass index in 21 (35%) have ≤25 kg/m2 and 39 (65%) have >25kg/m2. Mean VAS score was 4.27±2.09 and showed a significant association of pain between groups (p<0.001). Conclusion: Pain was found significantly lower in patients undergoing elective lower limb surgery with valsalva maneuver during spinal anesthesia.